Restoration of facadist intervention of the Figallo House Sullana (Peru) - Carbajal Bengoa, Fabio Samuel (Restauro Compás y Canto S.A., 2021)
The Figallo house is a building recognized as an Architectural Monument on April 26, 1989 by Resolución Jefatural 191-89-INC / J. Originally built with brick on the first level and quincha on the second level, it has a republican neoclassical style typical of the 1920s in Peru. It was intervened in the 1950s, during which the preservation of the buildings due to their typology or age was not important, the original interior of the house being demolished (becoming a case of façade) and the entire perimeter facade maintained, constructing a new building of brick walls, columns and reinforced concrete slabs to which the original exterior façade was attached. In 2012, due to structural construction failures, lack of maintenance, attack of xylophagous insects, damage caused by the El Niño phenomenon, a new interior demolition and the restoration of the original façade were necessary. The new construction considers a new use that forces the building to have three floors and a basement, which will be built respecting the existing openings, as well as its connection to the façade walls, leading to the restoration of quincha walls and the dome that is of the same material.